WA573

65 Reputation

3 Badges

0 years, 126 days

MaplePrimes Activity


These are questions asked by WA573

Why the expression of lambda[1] is too large? One of the possible values of lambda[1] should be "sqrt(1/(4*omega^2 - 4))*a[-1]". 

JCN.mw 

Why is the Maple giving this error. See attched file. Further, how can we eq. of the form "A+B`*sqrt(C) = 0" by eliminating the common denominator.

CM_TW.mw

Why Maple returns empty solution (see eq. (5))? Also, is it possible that Maple not only gives us the explit solution but also the solution steps?

restart

with(PDEtools, TWSolutions, declare)

[TWSolutions, declare]

(1)

with(DEtools, diff_table)

[diff_table]

(2)

U := diff_table(u(x, t))

table( [(  ) = u(x, t) ] )

(3)

sys := {U[]*U[x]+U[t]-pU[x, x]+qU[x, x, x] = 0}

{u(x, t)*(diff(u(x, t), x))+diff(u(x, t), t)-pU[x, x]+qU[x, x, x] = 0}

(4)

TWS_sol := TWSolutions(sys)

(5)

map(pdetest, [TWS_sol], sys)

[]

(6)

``

Download twsol.mw

How can we determine the highest (or peak) value for every hump and at what value of (x, t) in the plot?

peak.mw

How to find the dispersion relation (3) in Maple? I try it by equating the coefficients of cos(kx + wt) and its derivative to zero, but couldn't find it.

restart

with(LinearAlgebra):

alias(E = E(x, t), P = P(x, t), N = N(x, t), Q = Q(x, t));

E, P, N, Q

(1)

d := Matrix([[c*(diff(E, t))+diff(E, x), alpha*P, 0, 0], [N[0]*E, diff(P, t), -sigma[2]*Q[0]*N/N[0], sigma[2]*omega[0]*Q], [0, sigma[1]*sigma[2]*Q[0]*P/N[0], diff(N, t), 0], [0, -omega[0]*P, 0, diff(Q, t)]]) = 0

d := (Matrix(4, 4, {(1, 1) = c*(diff(E(x, t), t))+diff(E(x, t), x), (1, 2) = alpha*P(x, t), (1, 3) = 0, (1, 4) = 0, (2, 1) = N(x, t)[0]*E(x, t), (2, 2) = diff(P(x, t), t), (2, 3) = -sigma[2]*Q(x, t)[0]*N(x, t)/N(x, t)[0], (2, 4) = sigma[2]*omega[0]*Q(x, t), (3, 1) = 0, (3, 2) = sigma[1]*sigma[2]*Q(x, t)[0]*P(x, t)/N(x, t)[0], (3, 3) = diff(N(x, t), t), (3, 4) = 0, (4, 1) = 0, (4, 2) = -omega[0]*P(x, t), (4, 3) = 0, (4, 4) = diff(Q(x, t), t)})) = 0

(2)

re := -c*omega^3-kappa*omega^2+(c*omega[0]*(N[0]^2*sigma[2]+Q[0]^2*sigma[1])/N[0]^2-alpha*N[0])*omega+kappa*omega[0]*(N[0]^2*sigma[2]+Q[0]^2*sigma[1])/N[0]^2 = 0;

-c*omega^3-kappa*omega^2+(c*omega[0]*(Q[0]^2*sigma[1]+N[0]^2*sigma[2])/N[0]^2-alpha*N[0])*omega+kappa*omega[0]*(Q[0]^2*sigma[1]+N[0]^2*sigma[2])/N[0]^2 = 0

(3)

``

``

Download d_relation.mw

1 2 3 Page 1 of 3